OPPORTUNISTIC INFECTIONS IN PATIENTS WITH DIABETES MELLITUS - Masharipov S.M; Masharipova Sh.S (Western European Studies, 2025)
Diabetes mellitus (DM) is a chronic disease accompanied by impaired carbohydrate metabolism, which has a systemic impact on the immune system.This study aims to investigate the spectrum of opportunistic infections in 12 patients with type 2 diabetes mellitus aged 35- 50 years. The assessment was conducted based on the analysis of medical records, clinical examination, and the results of laboratory tests. The results showed a high frequency of respiratory and urogenital infections in this group of patients. The data obtained indicate the need for a comprehensive approach to the management of patients with type 2 diabetes mellitus, including the prevention and timely diagnosis of infectious diseases.
Keywords: Diabetes mellitus; opportunistic infections; immunity